1934. gada 15. maijā Latvijā notikušā apvērsuma juridisks raksturojums - Lakstīgala, Zanda (Latvijas Universitāte, 2012)
Maģistra darbs ,,1934. gada 15. maijā Latvijā notikušā apvērsuma juridisks raksturojums” sastāv no piecām nodaļām. Jēdziens ,,apvērsums” tika pētīts pirmajā nodaļā, tika apskatīti sinonīmi un vārdi ar līdzīgu nozīmi. Autore uzskata, ka minētie notikumi vairāk atbilst kriminātiesību zinātnes jēdzienam ,,dumpis”, jo ,,apvērsums” ir politikas zinātnes jēdziens. Otrajā nodaļā tika apskatīts varas dalīšanas princips. Jēdziens ,,varas dalīšana” ir mācība par varas dalīšanu likumdošanas, izpildu un tiesas varā. Trešajā nodaļā, autore apskata politisko situāciju pasaulē no 1917. gada līdz 1939. gadam. Pēc Pirmā pasaules kara Eiropā vadošā valsts pārvaldes forma bija demokrātija. Tomēr ar laiku demokrātiju kā valsts pārvaldes formu atzina nepietiekami efektīvu. Ceturtajā nodaļā galvenā uzmanība tika pievērsta 1922. gada 15. februārī pieņemtajai Satversmei, kas noteica, ka Latvija ir parlamentāra republika, līdz 1934. gada 15. maija K. Ulmaņa vadītajam valsts apvērsumam. Ministru prezidenta tiesības un kompetence tika analizēta piektajā nodaļā. Tika vērtētas K.Ulmaņa tiesības, kā ministru prezidentam, paralizēt Saeimas darbību, ierobežojot tai ar Satversmi noteiktās funkcijas. Kārlis Ulmanis bija nozīmīga personība Latvijas vēsturē, tomēr pārkāpjot likumu, viņam draudēja atbildība likuma priekšā.

Master’s thesis „Juridical Characteristics of the Coup in Latvia” consists of five chapters. Interpretations of the concept “coup” have been studied in the first chapter, and some synonyms or words with a similar meaning have been searched for. Great attention has been drawn to the adequacy of the usage of the concept that according to the author is not precise for it is a concept of political science. However, since the actions of Karlis Ulmanis were illegal and culpable, in the author’s opinion, it would be more appropriate to use the concept of jurisprudence, more precisely – criminal law – “rebellion”. The second chapter reflects on the principle of the separation of powers. The concept “separation of powers” is a study on the division of powers into an executive, a legislature, and a judiciary. In the third chapter, the author of the thesis has examined the events in the world during the period of 1917 to1939, considered political events and dissemination of diverse political regimes. After the World War I, many European countries’ type of state administration was democracy, which was very prestigious. However, there was a predominant view that democracy as a type of state administration was weak and ineffective, which also caused the dissemination of undemocratic types of state administration in many European countries. The influence of the economic crisis on the politics of the world’s countries has also been examined in the chapter, because the lack of a long-term economic sustainably impaired the functioning of democracy. In the fourth chapter, the Latvian political situation has been examined – greater attention has been drawn to the adoption of the Satversme on February 15, 1922, existence of Latvia as a parliamentary republic until the coup led by Karlis Ulmanis on May 15, 1934. Possible reasons for the coup have been analyzed in the thesis, which according to the author might be either imperfection of the Satversme or the world’s economic crisis that affected the providence of all world’s countries to great extent. An analysis of the rights of a Prime Minister has been carried out and their general boundaries have been examined in the chapter five. The author has also described the area of the authority of Karlis Ulmanis as Prime Minister, which he had violated by performing a rebellion, i.e. usage of the authority to intentionally change the system existing in Latvia and to overset the Saeima or to subtract its functions granted by the Satversme of the Republic of Latvia. Karlis Ulmanis was an important character during the time when Latvia was founded as a country; however, by performing a rebellion, he offended against the Law and was threatened by legal proceedings.
Juridical Characteristics of the Coup in Latvia
Keywords: Juridiskā zinātne